2013
DOI: 10.1080/09669582.2012.742531
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable tourism indicators: selection criteria for policy implementation and scientific recognition

Abstract: CIRANO Le CIRANO est un organisme sans but lucratif constitué en vertu de la Loi des compagnies du Québec. Le financement de son infrastructure et de ses activités de recherche provient des cotisations de ses organisations-membres, d'une subvention d'infrastructure du Ministère du Développement économique et régional et de la Recherche, de même que des subventions et mandats obtenus par ses équipes de recherche. CIRANO is a private non-profit organization incorporated under the Québec Companies Act. Its infras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
104
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(105 citation statements)
references
References 39 publications
0
104
0
1
Order By: Relevance
“…A large number of scholars and institutions proposed various indicator selection criteria [27,29,31,32]. In Tanguay et al's research work [31], two types of indicator selection criteria were identified: primary and secondary.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of scholars and institutions proposed various indicator selection criteria [27,29,31,32]. In Tanguay et al's research work [31], two types of indicator selection criteria were identified: primary and secondary.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of scholars and institutions proposed various indicator selection criteria [27,29,31,32]. In Tanguay et al's research work [31], two types of indicator selection criteria were identified: primary and secondary. The first type was planned to reduce the potential list into a feasible number and such criteria include classification, frequency of use, coverage of the main issues in tourism sustainability and measurability over time.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, our proposal is a system of sustainable tourism indicators which is scientifically valid and operational for decision-making, i.e., that provides indicators that have a high potential to be taken into account by managers in decisionmaking (Tanguay et al, 2013). Furthermore, our system provides a set of basic core indicators that can be adopted and implemented by the policy-makers from any destination for adopting management decisions.…”
Section: Definitionmentioning
confidence: 97%
“…The consideration of all these studies as a starting point ensures the scientific validity of our system, since the indicators in our initial list have been internationally set and agreed upon by experts in the field (Choi and Sirakaya, 2006;Tanguay et al, 2013).…”
Section: Definitionmentioning
confidence: 99%
“…Impacts cannot be avoided in tourism activities and hence, it is necessary to plan and manage the tourism resources in order to minimise the negative impacts and maximise the positive return of tourism (Archer et al, 2005). Research on sustainable tourism has been the concern of many authors (D'Hauteserre, 2010;Lim and Cooper, 2009;Soteriou and Coccossis, 2010;Tanguay et al, 2012;Williams et al, 2004). A new tourism attraction potentially reduces the quality of the environment and possibly impacts the socio-cultural life of the host people.…”
Section: Introductionmentioning
confidence: 99%